Antiproliferative efficacies but minor drug transporter inducing effects of paclitaxel, cisplatin, or 5-fluorouracil in a murine xenograft model for head and neck squamous cell carcinoma - Theile, Dirk; Gál, Zoltán; Warta, Rolf; Rigalli, Juan Pablo; Lahrmann, Bernd; Grabe, Niels; Herold-Mende, Christel; Dyckhoff, Gerhard; Weiß, Johanna (Cancer biology & therapy, 2014)
Drug-induced multidrug resistance (MDR) has been linked to overexpression of drug transporting proteins in head and neck squamous cell carcinoma (HNSCC) in vitro. The aim of this work was to reassess these findings in a murine xenograft model.
Gesehen am 29.09.2020